Seasons in the Russian-language writing of the Udmurt poet V. Ar-Sergi - Evgeniia V. Panteleeva (Publishing house "Sreda", 2023)
The article is devoted to the study of the semantics of the seasons in the Russian-language poetry of the Udmurt poet and prose writer V. Ar-Sergi. The relevance of this work is caused by the fact that today artistic texts of national authors require a holistic conceptual analysis, since they are strongly influenced by Russian literature, which in turn affects their ethnocultural identity. The issue of preserving, strengthening and developing national language in the multilingual space of the Russian Federation is acute. The author undertook an analytical review of the problem on the material of the Ar-Sergi Russian-language poetry. During the study, traditional methods of literary research (quantitative, structural-semiotic, comparison and collation, method of holistic text analysis) were used. Both traditionally mythological and individual authorial realia associated with the perception of calendar natural changes are reflected in the poetic texts of Ar-Sergi. The degree of their semantic connectedness with traditional canons of Udmurt culture is determined. Comprehension of the natural passage of time is closely intertwined with the emotional and psychological plan of the works. The natural landscape axiologically becomes a theme for constant artistic reflection in the poetry of Ar-Sergi. The lexical units from the lexico-semantic group "seasons" have not only a certain temporal semantic load but also denote the internal emotional state of the lyric subject in the poetic texts of the Udmurt poet. The attention of the author is turned not only on his own worldview but also folk-mythological contexts of the whole ethnic group.